Specification for thermal spray feedstock--solid and composite wire and ceramic rods (American Welding Society, 2002)
This specification provides the as-manufactured chemical composition classification requirements for solid and composite wires and ceramic rods for thermal spraying. Requirements for standard sizes, marking, manufacturing, and packaging are included.